Enhancement in the lift force of the Solid Fuel Ducted Ramjet (SFDR) with an increase in the controlling surface. (2022) - Kothari, Vishal; Mehta, Yash; Shrivastav, Dev; Panchal, Kishan
Abstract: The solid fuel ducted Ramjet systems (SFDR) are extremely capable of propelling high- speed missiles. They have a specific application in the configuration of air-to-air missiles with a high degree of interception. It is a modification from the traditional solid fuel ramjet system by using an external duct for thrust variation. This system provides higher effectiveness against maneuvering jets compared to single and dual pulse rocket system as it can vary thrust by varying fuel and air quantity for combustion. Even though with high effectiveness, an enemy fighter jet that is having higher thrust engines can outmaneuver SFDR by gaining significant lift during the end-stage which reduces its killing probability; this emphasized the development of a new missile system that provides more lift during the end-stage. A new SFDR concept is proposed in the present work that can gain more lift. The provision of a deflector is made in the duct to study the lift characteristics. Optimum lift force was obtained from the detailed analysis. Moreover, the study was extended by changing the deflector dimensions. Fluent fluid flow analysis is performed in simulation software named ANSYS to study the lift characteristics. Before that, 3D modelling is done with the help of NX software.